The shortage of medical workers in Sub-Saharan Africa and substitution policy - Arnaud Bourgain; Patrice Pieretti; Benteng Zou (Bielefeld University, Institute of Mathematical Economics (IMW), 2008)
Substitution policies are strategies sometimes chosen in Sub-Saharan Africa for curtailing the shortage of health professionals especially caused by the outflow of medical personnel. The aim of our contribution is to propose a way to assess the merits and drawbacks of substitution policies by developing a simple growth model of healthcare productivity with medical brain drain. Within this framework, we use a medical care production function of the CES type which aggregates low and high specialized health workers. We then run simulations which compare scenarios with and without substitution strategies by using data from the Ghana's medical sector.
urn:nbn:de:hbz:361-14192
Keywords: I18; F22; 330; Medical shortage; Healthcare policy; Substitution policy; Gesundheitswesen; Gesundheitsberufe; Brain Drain; Bottleneck; Gesundheitspolitik; Faktorsubstitution; Rationalisierung; Produktivität; Simulation; Theorie; Entwicklungsländer; Ghana